A decoupling control strategy for wind turbine blades equipped with active flow controllers. Issue 4 (15th September 2016) - Macquart, Terence; Maheri, Alireza; Busawon, Krishna
Abstract: The use of active controls has shown to be of substantial help in supporting the increasing size of wind turbines by reducing peak stresses and fatigue loads. In this respect, this paper proposes the use of intuitive frequency‐based control strategies for reducing loads in wind turbine blades equipped with multi‐input multi‐output (MIMO) active flow controllers. For that purpose, a loop‐shaping approach is considered for analysing the dynamic of actively controlled wind turbine blades. Preliminary aeroelastic simulations are carried out to validate the results. It is shown that the MIMO vibration control problem can effectively be decomposed into a number of decoupled single‐input single‐output control problems because of the strong correlation between the dominant aeroelastic blade dynamics and actuator deployments. As a result, it is demonstrated that classical single‐input single‐output control systems can perform as efficiently as MIMO controllers for damping the aeroelastic dynamics of wind turbine blades. Copyright © 2016 John Wiley & Sons, Ltd.